2007
DOI: 10.1002/aoc.1272
|View full text |Cite
|
Sign up to set email alerts
|

Alkynylorganotins, versatile precursors of class II hybrid materials

Abstract: In the field of functional organic-inorganic hybrid materials, recent trends in the chemistry based on trialkynylorganotins 1 and organically bridged α,ω-bis(trialkynyltin) compounds 2 are reviewed. Compounds 1 reacted with non-porous silica and nanoporous tin dioxide powders to yield hydrophobic, lipophobic or perylene dye-modified oxide materials. The formation of M oxide -O-Sn-C bonds and the release of three molecules of alkyne led to the irreversible chemisorption of 1, the reaction rate and the chain loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Furthermore, XRD (Figure a) and AFM (not shown) studies revealed that TF 120 was amorphous and made of aggregated hybrid particles as previously found for similar layer including a decylene spacer . As a result, the hydrolysis–condensation process was achieved, leading to the formation of an organotin-based hybrid layer with a local organization of the butylene spacer as reported for the bulk materials including longer alkyl chains …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, XRD (Figure a) and AFM (not shown) studies revealed that TF 120 was amorphous and made of aggregated hybrid particles as previously found for similar layer including a decylene spacer . As a result, the hydrolysis–condensation process was achieved, leading to the formation of an organotin-based hybrid layer with a local organization of the butylene spacer as reported for the bulk materials including longer alkyl chains …”
Section: Resultssupporting
confidence: 73%
“…63 As a result, the hydrolysis−condensation process was achieved, leading to the formation of an organotin-based hybrid layer with a local organization of the butylene spacer as reported for the bulk materials including longer alkyl chains. 75 Tin Oxide-Based Thin Film Characterization. Previous studies have shown that, on one hand, a calcination at a temperature higher than 450 °C was necessary to remove completely the butylene linker (according to FTIR and thermogravimetry coupled to mass spectrometry analyses), 67 and on the other hand, photochemical calcination was an efficient method to produce nanocrystalline porous oxide layers, 76,77 but the as-prepared TF 120 hybrid films were either annealed at 500−600 °C or treated under UV-irradiation in air to get tin oxide films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Newcomb’s group explored a series of organotin macrocycles and cages based on building blocks of composition Br­Ph 2 ­Sn–​(CH 2 ) n –​SnPh 2 ­Br ( n = 4, 5, 6, 8, 10, and 12) with the main objective to study their recognition properties for halide anions . The research group of Jousseaume synthesized a number of related dinuclear tetraorganotin compounds, but carrying aromatic connectors, some of which were then converted into polymeric organotin oxides . Jurkschat and co-workers prepared a series of macrocyclic ferrocenocyclophanes starting from 1,1′-Fe­(C 5 H 4 –​SiMe 2 ­CH 2 ­SnR 2 ­Cl) 2 (R = Me, Ph) , and, in collaboration with Dakternieks et al, a significant number of bis­(tetra­organo­distan­noxane)-based cages of variable sizes, which were derived mostly from different dinuclear organotin tetrahalides of composition X 2 RSn–​Y–​SnRX 2 (X = Cl, I, OTf; R = CH 2 ­CMe 3 , CH 2 CH­Me 2 , CH 2 ­SiMe 3 , Ph; Y = organic spacer group). In a conjunct research project between the Tuononen and Power research groups, more recently, an interesting tetranuclear cluster containing five ethylene moieties bridging four aryl substituted tin atoms and one tin–tin bond was achieved .…”
Section: Introductionmentioning
confidence: 99%
“…66 An analogous strategy has been used to elaborate and functionalise the surface of SnO 2 particles, by hydrolysis of XSn(CºCR) 3 in the presence of the nanoparticles, which resulted in attachment of XSn to the oxide surface. In this way, fluorinated chains [X = (CF 2 ) 7 CF 3 ] or dyes [X = (CH 2 ) n perylene, n = 2, 4], for applications in self-cleaning coatings and photovolataic devices, respectively, 67,68 have been prepared.…”
Section: Sol-gel Precursorsmentioning
confidence: 99%